A theory of mandatory convertibles - Chemmanur, Thomas J.; Nandy, Debarshi; Yan, An; Jiao, Jie (Journal of Banking & Finance, 2014)
The objective of this paper is to develop a theoretical analysis of “mandatory convertibles,” which are securities that automatically (“mandatorily”) convert to common stock on a pre-specified date. We consider a firm facing a financial market characterized by asymmetric information and significant costs in the event of financial distress. The firm can raise capital either by issuing mandatory convertibles, or by issuing more conventional securities like straight debt, ordinary convertibles, or equity. We show that, in equilibrium, the firm issues straight debt or ordinary convertibles if the extent of asymmetric information facing it is large, but the probability of being in financial distress is relatively small; it issues mandatory convertibles if it faces a smaller extent of asymmetric information but a greater probability of financial distress. Our model provides a rationale for the three commonly observed features of mandatory convertibles: mandatory conversion, capped (or limited) capital appreciation, and a higher dividend yield compared to common stock. We also characterize the equilibrium design of mandatory convertibles.